2016
DOI: 10.5851/kosfa.2016.36.6.699
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptability of Intramuscular Fat

Abstract: Fat in meat greatly improves eating quality, yet many consumers avoid visible fat, mainly because of health concerns. Generations of consumers, especially in the English-speaking world, have been convinced by health authorities that animal fat, particularly saturated or solid fat, should be reduced or avoided to maintain a healthy diet. Decades of negative messages regarding animal fats has resulted in general avoidance of fatty cuts of meat. Paradoxically, low fat or lean meat tends to have poor eating qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 82 publications
1
108
1
1
Order By: Relevance
“…However, the majority of sensory research on grass‐fed beef has only explored one or two biological types at a time. These include traditional beef breeds: Angus (O'Quinn et al., ), Wagyu (Frank, Joo, & Warner, ), Hereford (Realini, Duckett, Brito, Dalla Rizza, & De Mattos, ), and Simmental (Nuernberg et al., ); crossbreeds (Torrico et al., ); and some dairy cattle such as Holstein (Bjorklund, Heins, DiCostanzo, & Chester‐Jones, ). These studies come from all over the world, but there is very little current research examining acceptability of grass‐fed beef from different biological types in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of sensory research on grass‐fed beef has only explored one or two biological types at a time. These include traditional beef breeds: Angus (O'Quinn et al., ), Wagyu (Frank, Joo, & Warner, ), Hereford (Realini, Duckett, Brito, Dalla Rizza, & De Mattos, ), and Simmental (Nuernberg et al., ); crossbreeds (Torrico et al., ); and some dairy cattle such as Holstein (Bjorklund, Heins, DiCostanzo, & Chester‐Jones, ). These studies come from all over the world, but there is very little current research examining acceptability of grass‐fed beef from different biological types in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Although lncRNAs have gained increasing attention in recent years, understanding of how lncRNA affects intramuscular fat deposition in pigs is still limited due to the interspecies speci city of lncRNA, even though intramuscular fat is an economically important feature in determining meat quality [2]. Past studies have shown that lncRNAs are associated with fat deposition [16], and thus we proposed that lncRNAs may also be involved in the regulation of intramuscular fat deposition in pigs.…”
Section: Lnc_000368 Promotes Intramuscular Adipocyte Differentiationmentioning
confidence: 94%
“…Pork occupies an important part in the human diet as an important dietary protein source [1]. The intramuscular fat (IMF) content has been shown to be positively correlated with pork quality, as high intramuscular fat content can signi cantly improve the avor and tenderness of the pork [2]. However, in the last decades, extensive breeding selection aimed at increasing lean mass has resulted in low IMF and worsening avor, and thus increasing IMF has become an important concern in the pig breeding industry [3].…”
Section: Introductionmentioning
confidence: 99%
“…), distribution of intramuscular fat (IMF), referred to as marbling by customers, is closely related to meat quality, and a moderate increase in IMF benefits the taste and flavor of meat products [2]. The high content of intramuscular fat can increase the tenderness and flavor of pork [3]. Marbling develops either by an increase in adipocyte number, or adipocyte volume, or both.…”
Section: Introductionmentioning
confidence: 99%